PERBANDINGAN SIFAT FISIK SEDIAAN LILIN AROMATERAPI KOPI ROBUSTA (Coffea canephora) DAN KOPI ARABIKA (Coffea arabica) - Kurniasih, Trifonia Rosa; Sari, Dian Purwita; Maeshofa, Irna; Anggraini, Cristine; Harefa, Rai Madra Somasi; Sitompul, Lian Melissa (Jurnal Riset Kefarmasian Indonesia, 2024)
Coffee is a plant that has benefits that can reduce stress when applied to aromatherapy candles. There are two most popular types of coffee: robusta coffee (Coffea canephora), which has a more intense taste and aroma, and arabica coffee (Coffea arabica), which has a lighter taste and aroma. This research aimed to compare the physical properties of robusta coffee (FR) and arabica coffee (FA) aromatherapy candle preparations. The formulation of aromatherapy candle preparations had a paraffin base (10%), stearin, and composition of coffee oil and coffee powder, 2% and 2.5% for formula 1 and 10% and 10% for formula 2. Organoleptically, the candle was solid, not cracked, and had the color brown to black. The aroma of formula 1 was weak, and the aroma of formula 2 was strong, typical of coffee aroma. The burning time for candles with an average weight of 8.52 grams for each group for formulas 1 and 2 FA was 11.45 minutes and 10.04 minutes, while FR was 11.57 minutes and 9.57 minutes. The melting point for aromatherapy candles was an average of 52–54 °C. This value meets the criteria for candle preparations based on SNI. A comparison of the formulas for aromatherapy candle preparations had a significant effect on the weight and burning time of aromatherapy candle preparations. Overall, the coffee candle aromatherapy meets the SNI criteria for candle preparations.